Knowledge, attitude and practice of antenatal exercise among pregnant women in Hospital Universiti Sains Malaysia - Ling, Chua Yi (Universiti Sains Malaysia, 2014)
Exercise has been demonstrated to be beneficial for the mother and the unborn child, and programs of antenatal exercise for pregnant women have been recommended. There are few references on this subject in the literature. The aim of this study was to investigate the knowledge, attitude and practice of antenatal exercise among pregnant women in Hospital Universiti Sains Malaysia (Hospital USM). A cross-sectional, descriptive study was conducted in 128 pregnant women of 18 to 45 years of age receiving antenatal care at Hospital Universiti Sains Malaysia were surveyed using a structured self-administered questionnaire. The simple random sampling technique was used to select the sample for the study. Statistical analysis was conducted using the Statistical Package for Social Sciences (SPSS) version 20. Descriptive statistics were used to summarize socio-demographic and characteristics of the pregnant women. The Pearson’s chi-Square test was used to evaluate the association between the study variables: socio-demographic data (age, education level, number of pregnancy and income) with the knowledge, attitude, and practice of antenatal execise of pregnant women. A p-value of equal or less than 0.05 was considered significant. There was 56.3% (72) of study population had inadequate knowledge of antenatal exercise and 65.6% (84) participants had adequate attitude. Then, there was 53.9% (69) of participants had adequate practice while the remaining 46.1% (59) participants had inadequate practice. Educational level was found to be associated with the knowledge level of participants, with p-value 0.020. The two main sources of information regarding antenatal exercise are magazines (60.6%) and doctors (58.7%). There was 92.7% (114) participants claimed that antenatal exercise is necessary and important because it makes childbirth easier. Lack of information regarding antenatal exercise was the principal reason given by 29 (56.9%) participants for not exercising during pregnancy. This study reflected that there was a lack of knowledge in most of the pregnant women population. In comparison with the knowledge, attitude of pregnant women was higher regarding antenatal exercise. Besides that, These results suggest that the pregnant women’s knowledge concerning the antenatal exercise during pregnancy was inadequate and their attitude was favorable; there was nearly half of pregnant women not practiced antenatal exercises during pregnancy. Therefore, awareness regarding the benefit of antenatal exercise and related programme on exercise would be useful for pregnant women to practice antenatal exercise.